2003
DOI: 10.1097/00126334-200304010-00017
|View full text |Cite
|
Sign up to set email alerts
|

Virologic, Immunologic, and Clinical Response to Highly Active Antiretroviral Therapy: the Gender Issue Revisited

Abstract: We found no significant evidence of a gender difference in virologic, immunologic, or clinical outcomes after starting HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
78
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 30 publications
15
78
3
2
Order By: Relevance
“…Data on gender differences in trends of CD4 count after commencement of HAART are inconsistent. In line with the other studies report [23,24] we found no significant differences in CD4+ reconstitution regarding gender. But other reports indicated that females have better immunological reconstitution compared to males [25,26,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Data on gender differences in trends of CD4 count after commencement of HAART are inconsistent. In line with the other studies report [23,24] we found no significant differences in CD4+ reconstitution regarding gender. But other reports indicated that females have better immunological reconstitution compared to males [25,26,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, published data on determinants of response to HAART are often inconsistent. For example, women may [7,8] or may not [9] exhibit a better virological response than men. Low CD4 count at treatment initiation may be associated with better [8,[10][11][12] or poorer [13,14] immunological response.…”
Section: Introductionmentioning
confidence: 99%
“…This partly agrees with the work of Patterson et al, (2005), who purported that women may achieve virological suppression at a faster rate and have a better immune response than men on starting therapy most likely due to levels of endogenous female hormones, or other sex-linked factors. Sex differences in CD4 cell and clinical responses to HIV infection pre-HAART initiation (Prins et al, 1999;CASCADE Collaboration, 2003) and post-HAART initiation have been reported in some previous studies (Moore et al, 2002;Giordano et al, 2003aGiordano et al, , 2003bMocroft et al, 2000), but not all (Mocroft et al, 2003;Moore et al, 2003). Interestingly, the work of Patterson et al, (2007), show that immunological responses to HAART among previously antiretroviral-naïve patients appear to be similar across sex and age strata in the initial 6 months.…”
Section: Discussionmentioning
confidence: 75%